233k views
1 vote
Solve for substitution
y=-x-6
y=x+10

2 Answers

1 vote

Answer:

x=-4, y=-2

Explanation:

y+x=-6 --------- 1

y-x=10 ---------- 2

1 - 2

y + x - (y - x) = -6 -10

y + x - y + x = -16

2x = -16


x = ( - 16)/(2 )

x = -4

sub x=-4 to 1

y+(-4)=-6

y-4=-6

y=-6+4

y=-2

User Evergreen
by
5.5k points
4 votes
X=2 you do -x-6=x+10 then you add x to both side to cancel out the x with the negative sign in front. Then you get 2x+10=-6 then you subtract 10 on both sides then you get 2x=-16 then divide by 2 then x=-8
User RedFog
by
5.4k points